Dosimetric Comparison, Treatment Efficiency Estimation, and Biological Evaluation of Popular Stereotactic Radiosurgery Options in Treating Single Small Brain Metastasis - Duan, Yanhua; Cao, Hongbin; Wu, Boheng; Wu, Yinghui; Liu, Dong; Zhou, Lijun; Feng, Aihui; Wang, Hao; Chen, Hua; Gu, Hengle; Shao, Yan; Huang, Ying; et al. (Frontiers in Oncology, 2021)
Objectives: This study aimed to show the advantages of each stereotactic radiosurgery (SRS) treatment option for single small brain metastasis among Gamma Knife (GK), Cone-based VMAT (Cone-VMAT), and MLC-based CRT (MLC-CRT) plans. Materials and Methods: GK, Cone-VMAT, and MLC-CRT SRS plans were retrospectively generated for eleven patients with single small brain metastasis whose volume of gross tumor volume (GTV) ranged from 0.18 cc to 0.76 cc (median volume 0.60 cc). Dosimetric parameters, treatment efficiency, and biological parameters of the three techniques were compared and evaluated. The metric variation with the planning target volume (PTV) was also studied. Results: GK and MLC-CRT achieved a similar conformity index (CI), higher than Cone-VMAT. Cone-VMAT achieved comparable volume covered by 12Gy (V12) and gradient index (GI) as GK, lower than MLC-CRT. The heterogeneity index (HI) of GK, Cone-VMAT, and MLC-CRT decreased sequentially. GK gave the lowest volume covered by 3Gy (V3) and 6Gy (V6), while MLC-CRT got the highest. The Beam-on time and treatment time of GK, Cone-VMAT, and MLC-CRT decreased in turn. Tumor control probability (TCP) of all three SRS plans was greater than 98%, and normal tissue complication probability (NTCP) of all organs at risk (OARs) was below 0.01%. GK and Cone-VMAT resulted in superior TCP and NTCP of the normal brain tissue than MLC-CRT. The relative value of Cone-VMAT and GK for all metrics hardly changed with the target volume. Except for the unchanged HI and TCP, the other results of MLC-CRT with respect to GK improved as the target volume increased. MLC-CRT could produce higher CI than GK and Cone-VMAT when the target volume increased above 2 cc and 1.44 cc, respectively. Conclusion: For single small brain metastases, Cone-VMAT may be used as an alternative to GK-free centers. In addition to the advantage of short treatment time, MLC-CRT showed superiority in CI as the target volume increased. Treatment centers can choose appropriate SRS technique on a case-by-case basis according to institutional conditions and patients’ individual needs.